2010
DOI: 10.1177/1468794109348686
|View full text |Cite
|
Sign up to set email alerts
|

Using the telephone for narrative interviewing: a research note

Abstract: Much social science research dictates that the most productive mode for producing narrative data is through face-to-face interviews, with other modes of data production assumed to be ‘second best’. This research note makes a unique contribution to this debate by reflecting on a research project which used telephones to produce participant narratives. It draws on data from both the researcher’s field notes and the participants themselves, who were asked after the narrative interview about their experiences of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
321
1
16

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(352 citation statements)
references
References 9 publications
(11 reference statements)
14
321
1
16
Order By: Relevance
“…When compared to in-person interviews in other countries, it was felt that the online format made the adjustment of prearranged interview timing more likely than with in-person interviews. Similar experiences have been documented by other researchers who note that participants may feel less obliged to adhere to pre-agreed timings online than in person (Holt, 2010). The fluidity of the physical interview site and associated power dynamics will continue to evolve as technology and smartphones advance (Botha et al, 2010), and is particularly relevant to conducting interviews in inaccessible locations such as after a humanitarian emergency.…”
Section: Online Interviewingsupporting
confidence: 83%
“…When compared to in-person interviews in other countries, it was felt that the online format made the adjustment of prearranged interview timing more likely than with in-person interviews. Similar experiences have been documented by other researchers who note that participants may feel less obliged to adhere to pre-agreed timings online than in person (Holt, 2010). The fluidity of the physical interview site and associated power dynamics will continue to evolve as technology and smartphones advance (Botha et al, 2010), and is particularly relevant to conducting interviews in inaccessible locations such as after a humanitarian emergency.…”
Section: Online Interviewingsupporting
confidence: 83%
“…Finally, researchers have found that when interviewees were given the option, many chose the telephone instead of a face-to-face interview and were appreciative of being given the choice (Holt, 2010;Sturges and Hanrahan, 2004). Reasons for this preference was that with the telephone, interviewees perceive a greater level of anonymity and privacy than with face-to-face encounters (Carr and Worth, 2001;Holt, 2010;Sturges and Hanrahan, 2004).…”
Section: Counter Arguments In Favour Of Using the Telephonementioning
confidence: 99%
“…Reasons for this preference was that with the telephone, interviewees perceive a greater level of anonymity and privacy than with face-to-face encounters (Carr and Worth, 2001;Holt, 2010;Sturges and Hanrahan, 2004). The possibility of losing face is reduced and interviewees are more comfortable openly discussing personal opinions (Chapple, 1999;Opdenakker, 2006;Sturges and Hanrahan, 2004).…”
Section: Counter Arguments In Favour Of Using the Telephonementioning
confidence: 99%
See 2 more Smart Citations